2022
DOI: 10.1155/2022/7554133
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(VI) from Aqueous Solutions Using Biowastes: Tella Residue and Pea (Pisum sativum) Seed Shell

Abstract: The wide use of chromium (Cr) in different industries led to the release of a considerable amount of Cr(VI) into water bodies. Exposure to Cr(VI) can cause diseases in humans and animals. Therefore, low-cost technology for Cr(VI) removal is required. In this study, the biowastes, “Tella” residue (TR) and Pea (Pisum sativum) seed shell (PSS), were evaluated for their Cr(VI) removal efficiency from aqueous solutions. The physicochemical properties of adsorbents were studied, and the adsorbents were further chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…These results confirmed that the pseudo-second-order kinetic model was applicable and implied that electron sharing or electron transfer between PSD and Cr(VI) might be involved in this process. Similar kinetic fitting results have been reported for Cr(VI) adsorption [ 6 , 19 ].…”
Section: Resultssupporting
confidence: 86%
“…These results confirmed that the pseudo-second-order kinetic model was applicable and implied that electron sharing or electron transfer between PSD and Cr(VI) might be involved in this process. Similar kinetic fitting results have been reported for Cr(VI) adsorption [ 6 , 19 ].…”
Section: Resultssupporting
confidence: 86%
“…Biowaste materials such as avocado (Persea americana) seed (AS), enset (Ensete ventricosum) midrib leaf (EVML), barley (Hordeum vulgare L. (Poaceae) bran (BB), coffee (Coffea arabica L) residue (CR), "Tella" residue (TR), eucalyptus tree ash (ETA), acacia tree charcoal (ATC), pea (Pisum sativum) seed shell (PSS), and Erythrina abyssinica bark (EAB) locally called "Korch" were obtained from various locations of Jimma city, Ethiopia. "Tella" residue (TR) and the pea (Pisum sativum) seed shell (PSS) were treated as in literature [16]. Both AS and CR were obtained from local cafeterias, whereas BB, TR, ETA, ATC, and PSS were collected from local household wastes.…”
Section: Preparation Of Biowaste Materialsmentioning
confidence: 99%
“…Barley, maize, wheat, hops, and other spices are among the commonly used raw materials in the preparation of "Tella." Preparation of "Tella" requires 5-7 days, wherein the final stage, the potable "Tell" is filtered to remove any suspended solid while the settled residue is used to feed cows or discard [16].…”
Section: Preparation Of Biowaste Materialsmentioning
confidence: 99%
“…The filtrate was measured by AAS. The amount of chromium ions adsorbed per gram of adsorbent (mg/g) was calculated by the equation (Kebede et al 2022).…”
Section: Implementation Of C-oxw and C-oxds As An Adsorbentmentioning
confidence: 99%